2017
DOI: 10.1111/1742-6723.12837
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐related presentations to the Royal Perth Hospital Emergency Department: A prospective study

Abstract: 15.2% of patient presentations over the study week were alcohol-related. These patients were more likely to present with injury; one in five having injuries suspected to be caused by a third party affected by alcohol. This is a significant public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Injuries contributed to 50.5% of all alcohol‐positive presentations. However, the length of stay in the ED and admission rates were not different in comparison to alcohol‐negative presentations …”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…Injuries contributed to 50.5% of all alcohol‐positive presentations. However, the length of stay in the ED and admission rates were not different in comparison to alcohol‐negative presentations …”
Section: Methodsmentioning
confidence: 88%
“…The AHED study was a multi‐centre prospective observational cohort study conducted from 08:00 Monday 1 December 2014 to 08:00 Monday 8 December 2014 in eight EDs across Australia and New Zealand collecting clinical and demographic data of alcohol‐related ED presentations . The present study included RPH, an adult inner‐city tertiary referral hospital in Perth, Western Australia . In 2014, the annual census for RPH ED was 83 000 with a 43% admission rate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent multi‐site study in Australia and New Zealand identified that almost 10% of all emergency department (ED) attendances were alcohol related . Though there is no routine and reliable data on the numbers of women seeking emergency care who are both intoxicated and victims of violence, previous research indicates that up to two‐thirds of assault related presentations (both females and males) to EDs are alcohol‐related and that around 8% of alcohol‐related female presentations involve injuries from an assault . However, emergency care clinicians (nurses, doctors, paramedics and allied health who provide emergency care) have low levels of confidence in dealing with this vulnerable patient population .…”
Section: Introductionmentioning
confidence: 99%